2019
DOI: 10.1016/j.cortex.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spelling regularity on handwriting production: A coupled fMRI and kinematics study

Abstract: Current models of writing assume that the orthographic processes involved in spelling retrieval and the motor processes involved in the control of the hand are independent. This view has been challenged by behavioral studies, which showed that the linguistic features of words impact motor execution during handwriting. We designed an experiment coupling functional magnetic resonance imaging and kinematic recordings during a writing to dictation task. Participants wrote orthographically regular and irregular wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 83 publications
4
13
0
Order By: Relevance
“…In the case of children with more automatised graphomotor abilities, as we assume was the case for children in Grade 3 at the start of the study (coh2), the impact of graphic complexity on handwriting speed was already present at the start of the study and remained stable over time (Grades 3-5). Interestingly, while handwriting speed has often been interpreted as a reflection of orthographic processes (Sumner et al, 2013;Kandel and Perret, 2015;Palmis et al, 2019), this study provides a novel finding regarding the effect of graphic complexity on speed.…”
Section: Effect Of Word Orthographic and Graphic Complexity On Writing Developmentmentioning
confidence: 79%
See 2 more Smart Citations
“…In the case of children with more automatised graphomotor abilities, as we assume was the case for children in Grade 3 at the start of the study (coh2), the impact of graphic complexity on handwriting speed was already present at the start of the study and remained stable over time (Grades 3-5). Interestingly, while handwriting speed has often been interpreted as a reflection of orthographic processes (Sumner et al, 2013;Kandel and Perret, 2015;Palmis et al, 2019), this study provides a novel finding regarding the effect of graphic complexity on speed.…”
Section: Effect Of Word Orthographic and Graphic Complexity On Writing Developmentmentioning
confidence: 79%
“…Studies conducted in French have revealed that words' orthographic characteristics, especially regularity, influenced handwriting fluency in university students (Delattre et al, 2006) and in children from 8 to 10 years old (Kandel and Perret, 2015). The impact of orthographic complexity on handwriting execution has been demonstrated in adults by neuroimaging evidence (Palmis et al, 2019). The opposite direction of the relationship has also been investigated, revealing that the graphomotor demand was negatively related to grammatical spelling performance in French (Van Reybroeck and Hupet, 2009).…”
Section: Psycholinguistic Approach In Writing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Two motor areas (supplementary motor area (SMA), and the right precentral gyrus) were found to be preferentially activated for adults. The SMA is involved in movement control; its activation is reliably observed in writing tasks but its contribution is considered non‐specific (Palmis et al, 2019; Purcell, Napoliello, et al, 2011; Rapp & Dufor, 2011; Rapp et al, 2016). More generally, it is often mobilized in language production tasks (Longcamp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroscientific evidence also suggests that atrophy in the grey matter in the left insula, which is directly implicated in phonological encoding, is also a cause of TOT in old people (Shafto et al, 2007; see also Maril et al, 2001, 2005, for different neuroscientific findings regarding TOT). In handwriting, people experience more spelling difficulties for words of lower spelling regularity and for words with a higher homophone density (Kandel & Perret, 2015; Palmis et al, 2019; Planton et al, 2019; R. Wang et al, 2020; C.…”
Section: Empirical Research On Top and Character Amnesia In Chinese Handwritingmentioning
confidence: 99%